The Working Women's Travelling Trend in Covid 19 Post Pandemic Era - Sukirno, Zakaria Lantang Sukirno; Haroni, Nanang; Kulau, Febriansyah Kulau (Journal of Tourism and Creativity, 2025)
Women are one of the active segments of travelers. This research aims to explore the travel choices of working women. The type of research is exploratory to gain knowledge about post-pandemic travel trends. The results describe that unmarried working women prefer to travel independently or in small groups. Four types of tourist attractions are trending among the informants: nature tourism, cultural tourism, artificial tourism, and event tourism. Nature tourism is the main choice because it is in the open air. Other types of tourist attractions are also favored but are not the main choice for now. Travel is for fun, gaining knowledge, new experiences, shopping for souvenirs, especially local products, and relieving boredom from routine. Informants believe that post-pandemic tourism activities should still adhere to cleanliness, health, safety, and comfort. The post-pandemic era encourages informants to choose safe tourist attractions that meet CHSE standards, aiming to help the government's program in preventing the spread of the COVID-19 pandemic and promoting a healthy lifestyle.